(untitled) (Global Journal of Management and Business Research, 2016)
The performance management makes sure that employees are aware of the goal and objective that they have to achieve. The organization has certain goals and objectives. And it is the best in interest of organization of company and employee that the objectives of both must be in sync. Thus setting up objectives in advance helps the company and organization to be in same page. Further performance management helps the employee to grow with the company. Further this is a process that eliminate the difference and conflicts between the two. Performance management also helps in identifying key resource for the organization who can be rewarded and groomed to be the stars of the future (Walton, R 1985). Further performance management also helps in setting up the reward structure as to what kind of performance must get what kind of award. These incentives the employee to see what is expected and what in return they are going to get.